2012
DOI: 10.1080/09585192.2011.581634
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cultural dimensions as predictors of performance management preferences: the case of self-initiating expatriate New Zealanders in Belgium

Abstract: Despite the large number of New Zealanders working overseas of their own volition, the expatriate management literature has largely ignored their performance management (PM) preferences. The need to consider followers' preferences has been established by evidence supporting a link between PM practices and national culture, and subsequent performance. This study utilised the semi-structured interview to explore and compare the PM preferences of self-initiating expatriate New Zealanders in Belgium, and Belgians.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In terms of the studied SIEs’ move between home and host country, it can be observed that it mostly occurs between developed countries (e.g. New Zealand-Belgium: Ellis 2012 ), followed by developing to developed ones (e.g. China-Germany: Cao et al 2013 ) and very few take place between developed to developing countries (e.g.…”
Section: Comparing the Research Conducted Between 1997 And 2011 Versumentioning
confidence: 99%
“…In terms of the studied SIEs’ move between home and host country, it can be observed that it mostly occurs between developed countries (e.g. New Zealand-Belgium: Ellis 2012 ), followed by developing to developed ones (e.g. China-Germany: Cao et al 2013 ) and very few take place between developed to developing countries (e.g.…”
Section: Comparing the Research Conducted Between 1997 And 2011 Versumentioning
confidence: 99%
“…The criteria presented here could serve as a basis for a classification of the different samples found in research studies in order to determine what kind of subgroups of international movers were included in the migrant category and to better understand and interpret the results found. ; (Thorn, 2009); (Ellis, 2011); Long-term (N = 6) (O" Sullivan & years (N = 3) (Meyskens et al, 2009); (Konopaske, Robie, & Ivancevich, 2005); (Collings et al, 2007) Maximum Duration: 1 year (N = 3) (Collings et al, 2007); ; (Tharenou & Harvey, 2006), 3 years (N = 2) (Guzzo, 1994); (Dickmann & Harris, 2005) (Cappellen & (N = 2) (Konopaske et al, 2005); (Meyskens et al, 2009) Implication: Either relocation of family or not…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…Executing Work Abroad Findings: Individual (N = 14) (Fitzgerald & Howe-McKenna, 2000); (Forstenlechner, 2010); ; (Ellis, 2011); (Biemann & Andresen, 2010) Self-funding (N = 5) (Peltokorpi, 2008); ; ; ; (Tharenou, 2010) Implication: No or little support from employer High support from home and host organization…”
Section: Criteria: Organizational Level Findingsmentioning
confidence: 99%
See 2 more Smart Citations